Upaya Pencegahan Tindak Pidana Fraud di Perusahaan - Leony Cong; Zainudin Hasan (Journal of Management and Creative Business, 2024)
Corruption within companies is a serious challenge that can undermine integrity, reputation, and organizational performance. This article explores strategic measures to prevent corruption in corporate environments. Prevention involves implementing clear anti-corruption policies, providing training and education for all employees, and establishing secure and anonymous reporting systems. Regular internal audits, financial transparency, and the application of good corporate governance principles form the foundation of these efforts. Additionally, strict and consistent sanctions, leadership integrity, and continuous risk assessment are discussed as proactive approaches to reduce the potential for corruption. Through a comprehensive strategy, companies can create a work environment free from corrupt practices, supporting sustainable and ethical business growth.